Effect of Slow Deep Breathing on Blood Pressure of Elderly Hypertension - Aufa Zahra Fauziyyah; Norman Wijaya Gati (Universitas Duta Bangsa Surakarta, 2026)
Non-pharmacological treatments can include slow, deep breathing therapy this exercise can reduce the heart's workload by increasing oxygen (O?) supply, resulting in a decrease in heart rate and subsequent reduction in blood pressure. Objective; to analyze the difference in blood pressure before and after administering Slow Deep Breathing therapy to the elderly with hypertension. Methods: The method used was quantitative research with a Quasi-Experimental design. Sampling was conducted using a nonprobability sampling technique. The results of the Shapiro–Wilk normality test showed that the data were normally distributed, so data analysis was continued using a paired t-test. The experimental research sample was drawn using the simple Federer formula for 18 respondents. Results; The results of statistical analysis using a paired t-test on systolic blood pressure before and after the intervention showed that the p-value was 0.000 <0.05, while the diastolic blood pressure before and after also decreased with the same results, with a p-value of 0.000 <0.05. The hypothesis was accepted, so there was a significant difference. Conclusion: There is an effect of administering Slow Deep Breathing therapy on reducing systolic and diastolic blood pressure in elderly hypertensive patients.